2014
DOI: 10.1099/ijs.0.059766-0
|View full text |Cite
|
Sign up to set email alerts
|

Geothermomicrobium terrae gen. nov., sp. nov., a novel member of the family Thermoactinomycetaceae

Abstract: Geothermomicrobium terrae gen. nov., sp. nov., a novel member of the family Thermoactinomycetaceae Strains YIM 77562 T and YIM 77580, two novel Gram-staining-positive, filamentous bacterial isolates, were recovered from the Rehai geothermal field, Tengchong, Yunnan province, southwest China. Good growth was observed at 50-55 6C and pH 7.0. Aerial mycelium was absent on all media tested. Substrate mycelium was well-developed, long and moderately flexuous, and formed abundant, single, warty, ornamented endospore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Desmospora, Marinithermofilum, Hazenella) or environmental sources (e.g. Mechercharimyces, Lihuaxuella, Geothermomicrobium and Risungbinella) (Matsuo et al 2006;Yassin et al 2009;Yu et al 2012;Buss et al 2013;Zhou et al 2014;Kim et al 2015;Zhang et al 2015). Salient properties of the family Thermoactinomycetaceae include thermotolerant growth up to 60 °C, Gram positivity, non-acid fastness and formation of single spores that may be sessile or on simple sporophores with the structure and properties of endospores.…”
Section: Introductionmentioning
confidence: 99%
“…Desmospora, Marinithermofilum, Hazenella) or environmental sources (e.g. Mechercharimyces, Lihuaxuella, Geothermomicrobium and Risungbinella) (Matsuo et al 2006;Yassin et al 2009;Yu et al 2012;Buss et al 2013;Zhou et al 2014;Kim et al 2015;Zhang et al 2015). Salient properties of the family Thermoactinomycetaceae include thermotolerant growth up to 60 °C, Gram positivity, non-acid fastness and formation of single spores that may be sessile or on simple sporophores with the structure and properties of endospores.…”
Section: Introductionmentioning
confidence: 99%
“…Tsilinsky (1899) proposed a new genus Thermoactinomyces with the capacity to grow at high temperatures (50–55 °C), which was the first described member of the family Thermoactinomycetaceae (Matsuo et al , 2006). At the time of writing, on the basis of 16S rRNA gene sequence analysis, as well as chemotaxonomic and physiological characterization, the family Thermoactinomycetaceae accommodates 14 genera: Thermoactinomyces (Tsilinsky, 1899), Laceyella , Thermoflavimicrobium , Seinonella (Yoon et al , 2005), Planifilum (Hatayama et al , 2005), Mechercharimyces (Matsuo et al , 2006), Shimazuella (Park et al , 2007), Desmospora (Yassin et al , 2009), Kroppenstedtia (von Jan et al , 2011), Marininema (Li et al , 2012), Melghirimyces (Addou et al , 2012), Lihuaxuella (Yu et al , 2012), Hazenella (Buss et al , 2013), Polycladomyces (Tsubouchi et al , 2013) and Geothermomicrobium (Zhou et al , 2014). All known members of the family Thermoactinomycetaceae are Gram-positive, aerobic and thermophilic, with the exception of three mesophilic species, Seinonella peptonophila (Nonomura & Ohara, 1971; Yoon et al , 2005; basonym Thermoactinomyces peptonophilus ), Mechercharimyces mesophilus (Matsuo et al , 2006) and Shimazuella kribbensis (Park et al , 2007).…”
mentioning
confidence: 99%
“… * Data taken from: a , Park et al (2007); b , Zhou et al (2014); c , Yu et al (2012). † DPG, Diphosphatidylglycerol; PE, phosphatidylethanolamine; PG, phosphatidylglycerol; PI, phosphatidylinositol; PIM, phosphatidylinositol mannosides; PME, phosphatidylmethylethanolamine; AL, unknown aminolipid; APL, unknown aminophospholipid; PL, unknown phospholipid; L, unknown polar lipid; ‡ Ara, Arabinose; Gal, galactose; Glc, glucose; Man, mannose; Rha, rhamnose; Rib, ribose; Xyl, xylose. …”
mentioning
confidence: 99%
“…At the time of writing, 16 genera and 29 recognized species have been described in the family Thermoactinomycetaceae . The genera Shimazuella (Park et al , 2007), Desmospora (Yassin et al , 2009), Kroppenstedtia (von Jan et al , 2011), Melghirimyces (Addou et al , 2012), Lihuaxuella (Yu et al , 2012), Marininema (Li et al , 2012), Polycladomyces (Tsubouchi et al , 2013), Hazenella (Buss et al , 2013), Geothermomicrobium (Zhou et al , 2014) and Salinithrix (Zarparvar et al , 2014) have been found in succession and assigned to this family. Strains of this family have been isolated from various environmental samples, such as marine sediments, salt lakes, sugar cane, mushroom compost and clinical samples.…”
mentioning
confidence: 99%